2010
DOI: 10.5539/gjhs.v2n1p20
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Urban/Rural Differences of Public Health in China

Abstract: This research studies public health in China between urban and rural sectors and among the three geographic regions of the coast, inland and west. Similar to the situation of many other countries, public health in China is affected by economic development levels and the extent to which economic resources are distributed equitably in the three regions. In addition, China's economic reform in the last three decades has brought about tremendous changes in social structure and institutional arrangements that we ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Such development needs be more heavily emphasized in rural China. The institutional support for elderly persons in rural areas is non-existent and ineffective as the majority of the social service development and investment have been concentrated in urban areas (Li, 2010). This is evidenced in our results revealing an insignificant difference between elderly persons with perceived care support from a live-in care giver and those with no perceived support in rural areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such development needs be more heavily emphasized in rural China. The institutional support for elderly persons in rural areas is non-existent and ineffective as the majority of the social service development and investment have been concentrated in urban areas (Li, 2010). This is evidenced in our results revealing an insignificant difference between elderly persons with perceived care support from a live-in care giver and those with no perceived support in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Since the economic reforms in China, the government reduced spending on health care, which has greatly exacerbated the inequalities between urban and rural areas in China (Li, 2010). The urban-rural health care inequality has persisted because many of the recent health reforms have focused on urban areas (Li, 2010).…”
Section: Inequality In Institutional Social Support Provision In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion of studies from lower-resourced countries for the calculation of a pooled in-hospital mortality estimate may also explain why this estimate exceeds first-year mortality that is indicated by the pooled 1-year survival estimate. The heterogeneity identified within the WHO region sub-groups of in-hospital mortality estimates could be in part due to more micro-related differences in WHO regions such as different models of healthcare systems; specifically, urban versus rural, for which previous research has found discrepancies in health equity, especially in the case of China [34]. Although China is not considered a high-income country, reported in-hospital mortality was among the lowest compared to all other countries, which might reflect data availability from higher resource areas, such as Shanghai, and similarly resourced populations from a university hospital in Tianjin, China, as well as non-purposeful exclusion of more severe cases which, as detailed in the manuscript, were likely transferred to hospitals in nearby Beijing due to better medical facilities [111].…”
Section: Discussionmentioning
confidence: 99%
“…Country income level was included as a macro indicator, which was dichotomized into high income versus medium and low income due to limited number of studies in low-income countries [33]. Regional data from China were excluded from the meta-regressions as the national GDP is not representative of regional economic resources and related variation in accessibility, level and quality of specialized healthcare [34]. Publication and reporting biases were examined using a funnel plot and linear regression of the effect estimate on their standard errors [35].…”
Section: Methodsmentioning
confidence: 99%